Factors constituting effective communication: An empirical study of the food industry in Greece - Ioanna Grigoriou; Miltiadis Chalikias; Andreas Alexopoulos; Evangelos Karampotsis (Problems and Perspectives in Management)
This paper examines communication dynamics within the food industry to identify key factors enhancing organizational cohesion and efficiency. A structured survey was conducted among 152 employees drawn from a broader pool of 240 executives working in food-related enterprises (Thessaly, Greece). This study has unearthed 12 critical communication drivers that significantly influence workplace interactions. These include support and recognition, open and digital communication, trust and information exchange, information flow and benchmarking, effective communication, motivation and openness, positive updates, information and digital communication, transparency and conflict resolution, technology and information use, barriers and support, and communication in emergencies. The survey included 46 items, with 39 focusing on communication variables, and ensured data reliability with a Cronbach’s Alpha score of 0.883. Statistical methods such as principal component analysis and Kruskal-Wallis tests were used for analysis.Findings reveal significant challenges in internal communication, such as tensions between emotional and rational approaches, insufficient information sharing, and person-centered management practices, leading to employee frustration. Despite applying total quality management (TQM) principles, employees reported dissatisfaction with recognition and lack of two-way communication. External communication efforts, particularly transparency and marketing, engaged stakeholders but failed to fully build trust due to limited adherence to transparency principles. However, adopting professional standards and continuous feedback mechanisms has improved internal communication, leading to higher employee satisfaction and operational efficiency. The findings emphasize the need for tailored communication strategies that foster trust, collaboration, and align organizational goals with employee engagement, especially in industries with a localized, person-centered culture. AcknowledgmentsThis study was funded by Special Account Grants of University of West Attica.